2021
DOI: 10.1002/app.51878
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tribological properties of PEEK‐based composite coatings reinforced by PTFE and graphite

Abstract: The lubricating failure problems caused by friction and wear severely inhibit the regular operation and lifetime of artificial implanted joints. In order to improve their wear resistance effectively, the functional nano/micro-composite coatings consisted of poly(ether-ether-ketone) (PEEK)/graphite/polytetrafluoroethylene (PTFE) were successfully prepared through electrophoretic deposition and heat treatment. Additionally, the friction and wear behaviors under different loads and lubricating mediums of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…9 Among the many filler modifiers, Polytetrafluoroethylene (PTFE) is commonly used. [19][20][21][22][23] PTFE has low cohesion due to the repulsion of the negative charges of the fluorine atoms in its different molecular chains. During the friction process, the PTFE macromolecules are very easy to transfer to the friction surface.…”
Section: Introductionmentioning
confidence: 99%
“…9 Among the many filler modifiers, Polytetrafluoroethylene (PTFE) is commonly used. [19][20][21][22][23] PTFE has low cohesion due to the repulsion of the negative charges of the fluorine atoms in its different molecular chains. During the friction process, the PTFE macromolecules are very easy to transfer to the friction surface.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found that the addition of appropriate fillers is an effective method to reduce the friction coefficient and wear rate of PEEK, such as solid lubricants and nanoparticles [ 7 , 8 , 9 ]. PTFE is considered as one of the best fillers to improve wear resistance of PEEK-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending is one of the effective methods to improve the tribological performance of polymer materials. [ 8,9 ] In general, one polymer of the blending system is matrix, another polymer of the blending system is fillers. Such as PI/PTFE [ 9,10 ] and polytetrafluoroethylene/polyether ether ketone (PTFE/PEEK).…”
Section: Introductionmentioning
confidence: 99%